The short forms of HLA-G are unlikely to play a role in pregnancy because they are not expressed at the cell surface. - Bainbridge, DR; Ellis, SA; Sargent, I (2000)
HLA-G is a nonclassical class I MHC molecule of unknown function expressed on human invasive trophoblast. In trophoblast cells, HLA-G mRNA is alternatively spliced into a variety of forms which are predicted to encode a full length membrane-bound form, three short membrane-bound isoforms and two soluble isoforms. The aim of this study was to determine which of these protein isoforms are translated, which are expressed on the cell surface and which are secreted. Artificial cDNAs encoding the isoforms were generated by PCR mutagenesis, ligated to an epitope tag and transfected into a human cell line capable of expressing MHC class I. Protein products of appropriate sizes were detected in cells transfected with cDNAs encoding all membrane-bound forms, but surface biotinylation studies indicated that only full length membrane-bound HLA-G was present at the cell surface. Full length HLA-G was also detected by surface antibody binding and flow cytometry. Soluble HLA-G1 was detected in cells transfected with the appropriate cDNA only after treatment with monensin, which inhibits transport of glycoproteins through the Golgi apparatus. These results suggest that full length HLA-G, but not short HLA-G isoforms can be expressed on the surface of human cells and that soluble HLA-G is rapidly secreted. Thus, it is likely that the full length membrane-bound and soluble forms of HLA-G are the only biologically active forms to which the mother is exposed.